PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MAHASISWA PENDIDIKAN AKUNTANSI ANGKATAN 2009 MATA KULIAH AKUNTANSI PERPAJAKAN DI FAKULTAS EKONOMI UNIVERSITAS NEGERI SURABAYA - INDAH MARIAHYATI (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
Motivation is one think of psychology aspect in human self. The students have a high motivation will try do for time organize and schedule of learning until optimal result. However, at general motivation on study of Accounting Education Students 2009 in Economic Faculty University State of Surabaya is minus. When lecturing activity in class, the students were says that not dominate for matter giving to them. That the students asking about Tax Accountancy matter more difficult than another because more calculate and they must memorize of tax sections. The support students don’t asking a question if occurred difficulty experience. And only study if giving homework by university instructor. So desire for success isn’t enough, for studying need to motivate any more so that the student can touched them desire. The study aimed for investigating whether motivation on study huge influenced student achievement of Accounting Education Students in Economic Faculty University State of Surabaya.The study was associative with quantitaive approach. The analysis employed simple linear regression. The variables involved motivation on study as independent variable and achievement as dependent variable. The samples were taken by tired sampling. The study using lotttery so selected the students from Accounting Education 2009 grade B with total 40 students. The data were collected by conducting interview, documentation, and ditributing questionnaires.Simple linear regression showed that there was positive influenced between independent and dependent variables with regression equality that is Y=2,603+0,009X. F-test showed that simultaneous motivation on study did significantly influence achievement with side effect is 61%. Keywords: motivation study, achievement study